Autophagy: assays and artifacts - Barth, Sandra; Glick, Danielle; Macleod, Kay F (The Journal of pathology, 2010)
Autophagy is a fundamental and phylogenetically conserved self-degradation process that is characterized by the formation of double-layered vesicles (autophagosomes) around intracellular cargo for delivery to lysosomes and proteolytic degradation. The increasing significance attached to autophagy in development and disease in higher eukaryotes has placed greater importance on the validation of reliable, meaningful and quantitative assays to monitor autophagy in live cells and in vivo in the animal. To date, the detection of processed LC3B-II by western blot or fluorescence studies, together with electron microscopy for autophagosome formation, have been the mainstays for autophagy detection. However, LC3 expression levels can vary markedly between different cell types and in response to different stresses, and there is also concern that over-expression of tagged versions of LC3 to facilitate imaging and detection of autophagy interferes with the process itself. In addition, the realization that it is not sufficient to monitor static levels of autophagy but to measure 'autophagic flux' has driven the development of new or modified approaches to detecting autophagy. Here, we present a critical overview of current methodologies to measure autophagy in cells and in animals. Copyright © 2010 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.